Predictor Factors of Tuberculosis Treatment Success in Sleman Regency of Indonesia: Predictor Factors of Tuberculosis Treatment Success in Sleman Regency of Indonesia - Ida Safitri Laksanawati; Andriyanto, Eko; Wijayanti Subronto, Yanri (Medica Hospitalia : Journal of Clinical Medicine, 2022)
Background : Tuberculosis (TB) is the leading cause of mortality worldwide. Several studies have created risk scores to predict treatment success in TB patients. However, cohort study did not consider other clinical forms of TB, such as negative AFB smears and extrapulmonary TB. The objectives of this study was to knowing the predictor factors for the success of TB treatment in Sleman Regency by taking into account other  clinical forms of TB such as negative smear and extrapulmonary TB. Methods : The type and design of this study was an analytical study using a cross- sectional design conducted on TB patients in Sleman Regency from 2015 – 2018. Data were collected from TB 01 or TB 03 register of the Sleman District Health Office, including age, sex, BMI at the beginning of treatment, OAT (Antituberculosis Drugs) guideline, anatomic location, initial AFB status, AFB conversion status in intensive phase, type of TB patient, and treatment outcome. Chi-Square analysis and logistic regression were used to  determine the predictors of TB treatment success. Results : The research sample was 2308 people: 2158 successful treatments and 150 patients whofailed. AFB conversion in the intensive phase was the only variable to have a role in the TB treatment success (OR = 6.655, 95% CI: 3.354–13,207, p = 0.000). Conclusion : Conversion of AFB status in the intensive phase is a variable that contributes to the success of TB treatment. Age, sex, BMI at the beginning of treatment, OAT guidelines, anatomic location, initial AFB status, and type of TB patient are not predictors of TB success.